Analysis of Factors Affecting Job Satisfaction and Performance of Specialist Doctors - Samsinar Basri; Ratno Adrianto; Irfansyah Baharuddin Pakki (Indonesian Journal of Global Health Research, 2025)
There are many patient complaints regarding the performance of specialists at Kudungga Hospital. This is shown in accordance with the results of patient satisfaction surveys conducted in 2020 and 2021. From the satisfaction survey, it was concluded that the patient's complaint was the behavior of doctors who often arrived late so that the polyclinic schedule was not on time. The purpose of this study is to analyze factors related to job satisfaction and performance of specialist doctors at Kudungga Regional Hospital, East Kutai Regency.The type of research used is observational with a cross sectional design, namely a study that explores information about the phenomenon of work dissatisfaction of Specialist Doctors at Kudungga Sangatta Hospital and then analyzes the dynamics of the correlation between phenomena, between the independent variable and the dependent variable can be how far the influence between the independent variable on the dependent variable. The population and sample in this study were 30 specialist doctors who actively worked at the Kudungga Sangatta Regional General Hospital. Data collection was carried out by distributing questionnaires and collecting secondary data in the form of OPPE specialist doctors and And data analysis was carried out using univariate and bivariate analysis using the Spearman Rank test. There is a relationship between work environment conditions and promotion opportunities with job satisfaction of Specialist Doctors. Based on the results of data analysis and discussion, it can be concluded that factors related to specialist doctor job satisfaction consist of work environment conditions and promotion opportunities. The variable most closely related to specialist doctor job satisfaction is work environment conditions, which has an R value of 0.689 (a strong correlation).